Pertimbangan Hakim PN Banyuwangi dalam Menjatuhkan Putusan Terhadap Tindak Pidana Pencabulana Oleh Anak dibawah Umur: (Studi Putusan No 7/PID.SUS.A/2023/PN BYW) - Noviatul Hasanah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Fornication is all acts related to sexual life that violate decency (decency) including sexual intercourse outside of marriage. The Criminal Code classifies criminal acts of sexual abuse where the victim is a child. Children are the younger generation and potential human resources, therefore perpetrators of criminal acts of sexual abuse against children must be subject to appropriate punishment. The focus of the study in this research is to find out the side of justice in the decision of the panel of judges which is not in accordance with the actions of the defendant (Decision Study Number 07/Pid.Sus.A/2023/Pn Byw) case study of Banyuwangi Regency from the demands of the public prosecutor to the decision of the panel of judges what was imposed on the defendant was in accordance with the defendant's actions. From the results obtained in this research, the public prosecutor in his demands did not match the defendant's actions. The author feels that the panel of judges and public prosecutors in their decision gave criminal sanctions to the defendant that were not in accordance with the defendant's actions, because the perpetrator had more than one case.